Symbiotic crystal-glass alloys via dynamic chemical partitioning. (December 2021) - Wu, Ge; Liu, Chang; Brognara, Andrea; Ghidelli, Matteo; Bao, Yan; Liu, Sida; Wu, Xiaoxiang; Xia, Wenzhen; Zhao, Huan; Rao, Jing; Ponge, Dirk; Devulapalli, Vivek; et al.
Graphical abstract: Abstract: The design of high performance structural materials is always pursuing combinations of excellent yet often mutually exclusive properties such as mechanical strength, ductility and thermal stability. Although crystal-glass composite alloys provide better ductility compared to fully amorphous alloys, their thermal stability is poor, due to heterogeneous nucleation at the crystal-glass interface. Here we present a new strategy to develop thermally stable, ultrastrong and deformable crystal-glass nanocomposites through a thermodynamically guided alloy design approach, which mimics the mutual stabilization principle known from symbiotic ecosystems. We realized this in form of a model Cr-Co-Ni (crystalline)/Ti-Zr-Nb-Hf-Cr-Co-Ni (amorphous) laminate composite alloy. The symbiotic alloy has an ultrahigh compressive yield strength of 3.6 GPa and large homogeneous deformation of ∼15% strain at ambient temperature, values which surpass those of conventional metallic glasses and nanolaminate alloys. Furthermore, the alloy exhibits ∼200 K higher crystallization temperature ( TX > 973 K) compared to that of the original TiZrNbHf-based amorphous phase. The elemental partitioning among adjacent amorphous and crystalline phases leads to their mutual thermodynamic and mechanical stabilization, opening up a new symbiotic approach for stable, strong and ductile materials.